3 years ago the age of Abhishek was four times the age of sweta after 5 years the age of Abhishek will be two times the age of sweta
Answers
→
☛
☛
→
♦Let the age of Abhishek be x years
♦Let the age of Shweta be y years
→
Case1. : Age three years ago
→ (x - 3 ) = 4 (y - 3)
→ x - 3 = 4y - 12
→ x - 4y + 9 = 0 ...............[Eq.1]
Case2. : Age five years hence
→(x + 5 ) = 2(y+5)
→ x + 5 = 2y + 10
→ x - 2y - 5 = 0.............[Eq.2]
Applying ,
As the coefficient of x is already same , so just Subtract the two equations to eliminate x variable . Signs will also change while subtracting . so we have ,
=> x - 4y + 9 = 0
=> x - 2y - 5 = 0
----------------------------
= -2y + 14 = 0
2y = 14
Substitute this value of x in equation (1)
=> x - 4y + 9 = 0
=> x - 4(7) + 9 = 0
=> x - 28 + 9 = 0
=> x - 19 = 0
___________________________________________________
Answer:
the underline words are the
Step-by-step explanation:
I hope this is helpful for you
![](https://hi-static.z-dn.net/files/db8/498b203168851843cc7c885db0724995.jpg)
![](https://hi-static.z-dn.net/files/d41/e35462f5891621b2dde693b548bb0039.jpg)